ANALISIS KEPUASAN TERHADAP KUALITAS PELAYANAN PADA BENGKEL MOBIL NEGRO PALEMBANG SUMATERA SELATAN - Mujito; Rani Destriana; Benny Osta Nababan; Muhlis (Economicus, 2023)
This research aims to determine the level of service performance and consumer expectations as well as service indicators that are the company's priorities. This type of research is quantitative descriptive research. The number of samples is 100 samples with data analysis including service quality analysis, CSI analysis and IPA analysis (Importance Performance Analysis). The research results show that: (1) Based on the results of the gap analysis, it can be seen that almost all indicators have negative values. There is 1 indicator that has a positive value, namely indicator number 7, namely: "Negro Car Repair Mechanics in Palembang, South Sumatra provide accurate information regarding workshop services" with a percentage value of 102.47%, which means that for this indicator consumers feel very satisfied. Meanwhile, other indicators have a negative sign, which means that services related to these other indicators have not 100% met consumer expectations. (2) The results of the CSI analysis show that the CSI value is 70.67%. Based on the CSI analysis assessment criteria, this figure is in the quite satisfied criteria, this shows that consumers or service users at the Negro Palembang South Sumatra workshop feel quite satisfied with the service performance provided by the company, in this case the Palembang Negro South Sumatra workshop. (3) Service performance indicators that are a priority for improvement are indicators that are in quadrant I on the Cartesian diagram of IPA analysis (Importance Performance Analysis).